Image processing and Biometric Approach for Licence and Vehicle documents verification (International Journal of Engineering and Computer Science, 2017)
Fingerprints are rich in details which are in the form of discontinuities in ridges known as minutiae and are unique for each person. One of the most important tasks considering an automatic ﬁngerprint recognition system is the minutiae biometric pattern extraction from the captured image of the ﬁngerprint. The ﬁngerprint matcher compares features by using Digital Image processing from input search point against all appropriate driving licences in the database to determine if a probable match exists. An extended approach of digital image processing is used for Extraction of vehicle number plate. Information from the number plate is extracted and can be used in many applications like toll payment, parking fee payment. Currently we are implementing this system for only Standardized Indian number plates. In future it can be implemented for number plates with different fonts, shapes and size. Using this method, vehicle documents are veriﬁed. With this implementation, there’ll be no need to carry documents along. A single ﬁnger print and an image will be enough to recognise and verify the individual and the vehicle.